2018
DOI: 10.1002/lt.25011
|View full text |Cite
|
Sign up to set email alerts
|

Improved portal vein venoplasty with an autogenous patch in pediatric living donor liver transplantation

Abstract: A stenotic or hypoplastic portal vein (PV) represents a challenge for PV reconstruction in pediatric living donor liver transplantation (LDLT). Several PV venoplastic techniques have been developed. However, we still seek improved venoplastic techniques with better efficacy and compatibility. From June 2016 to July 2017, 271 LDLT procedures were performed at the Department of Liver Surgery, Renji Hospital. A total of 16 consecutive children with stenotic and sclerotic PVs underwent a novel technique-the autoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Although patch venoplasty for a stenotic PV is one of the standard techniques [ 1 , 19 ], it is necessary to evaluate its effectiveness. Many illustrations and intraoperative photographs have depicted the insertion of a narrow rectangular patch [ 1 ], but such a narrow patch can increase the PV diameter only by one-third of the patch width because it becomes a part of the PV circumference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patch venoplasty for a stenotic PV is one of the standard techniques [ 1 , 19 ], it is necessary to evaluate its effectiveness. Many illustrations and intraoperative photographs have depicted the insertion of a narrow rectangular patch [ 1 ], but such a narrow patch can increase the PV diameter only by one-third of the patch width because it becomes a part of the PV circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Vein allografts have been used in the present study. In contrast, a Chinese high-volume pediatric LT center presented a technique for autogenous PV patch plasty [ 19 ]. Vessel patches were procured from the left branch or the bifurcation of the right branch and left branch of the PV in the native liver.…”
Section: Discussionmentioning
confidence: 99%
“…Especially cryopreserved vascular grafts may result in portal vein complications in long term 15 . In addition, some authors suggested venoplasty to increase portal vein diameter 16,17 . During venoplasty, if sclerotic site is not resected, it might result in portal vein thrombosis 10 …”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, some authors suggested venoplasty to increase portal vein diameter. 16,17 During venoplasty, if sclerotic site is not resected, it might result in portal vein thrombosis. 10 One of the limitations of this study is due to the fact that it is a retrospective analysis and the available data for analysis were limited.…”
Section: Discussionmentioning
confidence: 99%
“…As for recipients, initial immunosuppressive therapy consisted of a dual drug regimen of tacrolimus combined with methylprednisolone. Doppler ultrasound (US) tests estimating the vascular system were performed daily in the first week after LT, every 2 days in the second week, monthly during the first 6 months, and every 3 months thereafter [ 7 ].…”
Section: Methodsmentioning
confidence: 99%